A rare case of long-term graft complication in a patient of middle aortic syndrome (Indian Journal of Case Reports, 2018)
Middle aortic syndrome (MAS) is rare entity described as a progressive narrowing of the aorta between the aortic arch and terminal bifurcation of the aorta. Surgical treatment is with the use of grafts for bypassing the narrow aortic segment. Rarely, graft complications may occur over long periods of time due to the axial growth of the patient and loss of tensile strength of the graft material. This is a case of MAS, presenting 34 years after initial surgery due to aneurysmal dilation of the graft, treated with redo surgery and complete recovery of the patient.